ANALISIS LENDUTAN MODEL SISTEM CAKAR AYAM MODIFIKASI DENGAN PEMBEBANAN TUNGGAL (BEBAN TITIK) - Lutfi Ahmad Yudandi; Bambang Setiawan; Noegroho Djarwanti (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2019)
Soft soil has low bearing capacity and high compressibility that can cause instability and long-term degradation that can make around some road settlement or wavy. A solution to prevent this soft soil problem was built Modified Chicken Foot, The function of Chicken Foot Foundation is to increase its bearing capacity. This research is using single load with variation distance of triangle foot foundation pattern whereas analysis of deflection using finite element method based. The research shows displacement result is depend on distance between load position and foot foundation, the closer distance between foot foundation the less it would result. The displacement result that happened at roadside is larger than at middle of the road, the difference between them is -6,8% up to 67% and The displacement result that happened in plate without pipe is larger than a plate with pipe, the difference between them is 12,31% up to 59,41%.